Методы планирования нейрохирургических доступов - Тымкович, М. Ю.; Аврунин, О. Г.; Фарук, Х. И. (НТУ "ХПИ", 2014)
В работе рассматриваются вопросы, связанные с разработкой компьютерной системы планирования нейрохирургических вмешательств. Одной из важных составляющих является определение значения инвазивности хирургического доступа. Рассмотрены различные подходы к определению инвазивности нейрохирургических доступов, выявлены их недостатки и преимущества. Показано, что карта инвазивности мозга человека является эффективным подходом при определении риска хирургического доступа.

The paper explores the issues that related to the development of a computer system planning of neurosurgical interventions. One of the most important parts is the process of determining the invasiveness of surgical access. Considered various approaches to the definition of invasive neurosurgical accesses identified their advantages and disadvantages. The study conclusions were drawn. The map of invasiveness of brain structures is an effective approach for determining risk of surgical access. Choice of surgical approach should take into account the geometry of the surgical instrument and error of positioning of stereotactic system. Choosing a surgical approach should take into account the possible displacement of brain structures, in accordance with the type of trepanation. Also must take into account the standard surgical approaches. These methods should allow significantly improve the quality of neurosurgical interventions.
Planning methods of neurosurgical accesses
Keywords: инвазивность доступа; хирургический доступ; нейрохирургическое вмешательство; system of planning; invasiveness of access; surgical access; neurosurgical intervention